IECON 2019 - 45th Annual Conference of the IEEE Industrial Electronics Society 2019
DOI: 10.1109/iecon.2019.8926673
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Design of a 1.2 pF Common-Mode Capacitance Transformer for Powering MV SiC MOSFETs Gate Drivers

Abstract: This paper proposes a physics-level modeling method for analyzing the primary to secondary-side (commonmode) parasitic capacitance of the transformer for the Mediumvoltage SiC MOSFETs gate drivers. The lumped circuit-based physics-model of the turn-to-turn capacitance, turn-to-core capacitance, and self capacitance of the core are derived, and it is found that the turn-to-core capacitance mainly contributes to the total equivalent parasitic common-mode capacitance. The measured common-mode impedance of the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Since the voltage potential is discrete in (3), the sum sequence is used to represent the total equivalent capacitance. In the limit of many turns, the sum can be approximated as an integral and C total (N) can be presented as (4).…”
Section: Fig3 Simplified Equivalent Circuit Using the Energy Conservation Methodsmentioning
confidence: 99%
“…Since the voltage potential is discrete in (3), the sum sequence is used to represent the total equivalent capacitance. In the limit of many turns, the sum can be approximated as an integral and C total (N) can be presented as (4).…”
Section: Fig3 Simplified Equivalent Circuit Using the Energy Conservation Methodsmentioning
confidence: 99%
“…As introduced in the previous section, the isolated transformers will have several parasitic capacitive couplings. Especially for gate drivers, the common-mode parasitic capacitance between the primary side and secondary side is the most significant due to the large dv/dt variations across the isolation of transformers [228]. Generally, reducing the overlapping area [229] and introducing the larger gap [152] to reduce turn-to-core capacitance as described above are the effective approaches to reduce CM parasitic capacitance.…”
Section: Gate Driversmentioning
confidence: 99%
“…Since tm is usually very small, the static capacitance between two adjacent layers is usually very large, according to (7). Then the dynamical capacitance Cll-par of the exampled two-winding copper-foiled inductor can be calculated as eq.…”
Section: B Copper-foil-based Inductors With Two Windingsmentioning
confidence: 99%
“…Passive components are essential in power electronics converters [1], [2]. For the converters utilizing wide-bandgap devices [3], [4], the parasitic capacitance in magnetic components, including inductors [5], [6], transformers [7] and motors [8], is of significant importance due to the fast switching characteristics (high dv/dt value) of the wide-bandgap devices [8], [9]. It is reported that such parasitic capacitance can significantly contribute to the capacitive current during the switching transients [10] and may result in increased conducted noise and extra switching losses dissipated by the transistors [11]- [14].…”
Section: Introductionmentioning
confidence: 99%